Studying the Effects of the External Forces on 1U CUBESAT - شيحا بلال; صبيرة ربيع (Latakia University Journal -Engineering Sciences Series, 2021)
This search studies the external forces affecting on a 1U CUBESAT with dimensions 10*10*10 at low altitude ranging from 200km to 600km, by weight 1.33kg, which are formed in the form of attractive moments and centrifugal moments, and we calculate the values of the orbital parameters, which includes angular velocity, orbital velocity, orbit time and shadow time for the CUBESAT by using MATLAB/R2014a environment. The orbit nature which the CUBESAT movement in it is circular and have polar inclination which evaluated approximately , to covering the area of Syria. This search showed that orbit altitude increasing of the forces torques with the exception of the solar pressure torque whose value are related to front surface area of the CUBESAT, as well as the value of atmospheric density when high solar radiation activities increase the value of the aerodynamic torque as well as magnetic torque. When the weight of CUBESAT increase from 1kg to 1.33kg with keeping the same dimensions of the CUBESAT, the magnetic torque, aerodynamic torque and gravity gradient torque are increased, but the solar pressure torque doesn’t effected in these increasing and the angular velocity and orbital velocity increased.